The Sopranos. Season six, Part I [videorecording (DVD)] - Weiner, Matthew; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie; Imperioli, Michael, 1966-; Chianese, Dominic, 1931-; Van Zandt, Steve (HBO Video, 2006)
Tony Soprano is a middle-aged, Italian-American businessman in New Jersey with a wife, a daughter, a son, and an elderly mother. He's got a psychiatrist to tell all his secrets to, except the one she already knows. He's also a mob boss facing several crises. Rival boss Johnny Sack is in prison and the always tense relations between the New Jersey and New York families are strained through the unpredictable behavior of Sack's surrogates.